Elaborations on (a) Decolonising Africa(n)-centred Feminist Psychology - Ratele, Kopano; Malherbe, Nick; Cornell, Josephine; Day, Sarah; Helman, Rebecca; Makama, Refiloe; Titi, Neziswa; Suffla, Shahnaaz; Dlamini, Sipho (PINS-Psychology in Society, 2020)
In a previous article we sought to clear up some of the conceptual confusion on African psychology whilst simultaneously engaging with what it entails to do a decolonising African psychology. We dealt with questions such as: Is African psychology identical to psychology in Africa? What is the main dispute between Africa(n)-centred psychology and Euroamerican-centric psychology in Africa? Might ‘Blackening’ psychology decolonise the discipline? And what can be gained from imbricating decolonising perspectives and feminist Africa(n)-centred psychology? In addition to the necessary work aimed at countering coloniality in psychology through thinking the world from Africa and the global South, that article began to invent a certain kind of writing as method – including story-telling, facilitation, dialogues, interruptions and mutual learning. We have since deepened on that method and, in this contribution, while seeking to elaborate on the last question in particular, that is to say, what is to be gained from closely linking and diffracting psychology through a prism of decoloniality, Africa(n)-centredness and feminism, the plan is to enact aspects of a decolonising method.